Abuse and misuse of antidepressants - Evans EA; Sullivan MA (Dove Medical Press, 2014)
Elizabeth A Evans, Maria A Sullivan Department of Psychiatry, Columbia University College of Physicians and Surgeons, New York, NY, USA Background: Rates of prescription drug abuse have reached epidemic proportions. Large-scale epidemiologic surveys of this under-recognized clinical problem have not included antidepressants despite their contribution to morbidity and mortality. The purpose of this review is to look specifically at the misuse of antidepressants and how this behavior may fit into the growing crisis of nonmedical use of prescription drugs. Methods: We conducted a comprehensive search on PubMed, Medline, and PsycINFO using the search terms “antidepressant”, “abuse”, “misuse”, “nonmedical use”, “dependence”, and “addiction”, as well as individual antidepressant classes (eg, “SSRI”) and individual antidepressants (eg, “fluoxetine”) in various combinations, to identify articles of antidepressant misuse and abuse. Results: A small but growing literature on the misuse and abuse of antidepressants consists largely of case reports. Most cases of antidepressant abuse have occurred in individuals with comorbid substance use and mood disorders. The most commonly reported motivation for abuse is to achieve a psychostimulant-like effect. Antidepressants are abused at high doses and via a variety of routes of administration (eg, intranasal, intravenous). Negative consequences vary based upon antidepressant class and pharmacology, but these have included seizures, confusion, and psychotic-like symptoms. Conclusion: The majority of individuals prescribed antidepressants do not misuse the medication. However, certain classes of antidepressants do carry abuse potential. Vulnerable patient populations include those with a history of substance abuse and those in controlled environments. Warning signs include the presence of aberrant behaviors. Physicians should include antidepressants when screening for risky prescription medication use. When antidepressant misuse is detected, a thoughtful treatment plan, including referral to an addiction specialist, should be developed and implemented. Keywords: antidepressant, prescription, misuse, abuse, nonmedical use, dependence, addiction